Structural diversity of five new bitriazole-based complexes: luminescence, sorption, and magnetic properties. Issue 3 (20th November 2014) - Du, Li-Yun; Wang, Hui; Liu, Ge; Xie, Dong; Guo, Fu-Sheng; Hou, Lei; Wang, Yao-Yu
Abstract : Employing a new bitriazole ligand, five complexes were assembled that display diverse structures, selective CO2 /CH4 adsorption, luminescent sensing, and antiferromagnetic properties. Abstract : Employing an uninvestigated eight N-donor bitriazole ligand, 5′-(pyrazin-2-yl)-2 H, 4′H-3, 3′-bi(1, 2, 4-triazole) (H2 pzbtz), five complexes, [Zn2 (pzbtz)(SO4 )(H2 O)2 ]·2H2 O n (1 ), [Cd(pzbtz)]·3H2 O n (2 ), [Zn3 (Hpzbtz)2 (SO4 )2 (H2 O)6 ] (3 ), [Co(Hpzbtz)2 (H2 O)2 ] (4 ) and [Co2 (pzbtz)2 (H2 O)2 ]·4H2 O n (5 ), have been solvothermally synthesised by altering the reaction solvents and temperatures. Complex1 shows a three-dimensional (3D) framework with a very rare (3, 5)-connectedfsc -3, 5- Cmce -2 topology. Complex2 exhibits a (4, 4)-connected 3Dpts framework with 1D channels. Complexes3 and4 are discrete trinuclear and mononuclear molecules, respectively. Complex5 presents a chiral 3D framework based on a novel trinuclear Co3 (tr)4 cluster and features an unusual six-connectedlcy topology. In the five complexes, H2 pzbtz show a very variety of geometrical configurations and coordination modes. Due to the planarity of H2 pzbtz, complexes1–3 display strong photoluminescence; in particular, 1 features highly selective luminescent sensing for the Cu 2+ ion and nitrobenzene molecule. In addition, 2 shows highly selective adsorption for CO2 over CH4, and5 exhibits antiferromagnetic exchange interactions among the Co 2+ ions.